Metabolic characteristics of human adipose tissue in vivo. - Frayn, K; Coppack, S; Humphreys, S; Whyte, P (1989)
1. A method was developed for sampling the venous drainage from the subcutaneous adipose tissue of the anterior abdominal wall. This is a large depot in many subjects, and seems well suited to such studies as it is completely separated from the venous drainage of the underlying muscle by the aponeurosis of the external oblique muscle. 2. Eight normal subjects were studied after an overnight fast, and for 120 min after ingestion of 75 g of glucose. Concentrations of substrates in the abdominal wall drainage were compared with those in arterialized blood and in forearm muscle drainage. 3. Non-esterified fatty acid and glycerol concentrations in the abdominal wall drainage were high (three to four times the arterial level) after overnight fast. After glucose ingestion, arterial and abdominal venous levels fell and the arteriovenous differences narrowed. The forearm showed uptake of non-esterified fatty acids when fasting but not after glucose ingestion, with no significant arteriovenous difference for glycerol at any time. 4. The abdominal wall tissues showed a small arteriovenous difference for glucose uptake during fasting, which increased after glucose ingestion. Although lactate was produced throughout, its molar ratio to glucose uptake was less than that reported for other superficial sites, suggesting only a minor contribution of skin metabolism. Forearm muscle showed a larger and more prolonged increase in arteriovenous difference for glucose uptake after the glucose load, but no consistent release or uptake of lactate. 5. We conclude that the tissue studied by this technique is predominantly adipose. This technique may have wide application in studies of the metabolic basis for body weight regulation in man.